2006
DOI: 10.1109/esscir.2006.307613
|View full text |Cite
|
Sign up to set email alerts
|

Integrated RF Front-End in 0.13 ¿m CMOS for Automotive and Industrial Applications beyond 20 GHz

Abstract: An integrated front-end, for automotive and industrial applications beyond 20 GHz, in 0.13 µm standard CMOS is presented. The front-end chip includes a low noise amplifier, a transformer-based Gilbert-mixer, an intermediate frequency amplifier and a buffer for the local oscillator input. The differential front-end at 22.5 GHz, measured on test-board, achieves a gain of 25.8 dB, a SSB noise figure of 6.8 dB, an input IP3 of -34.6 dBm and an input 1 dB compression point of -41.5 dBm while consuming 112.5 mW at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, drain and gate current noise as well as their correlation are thoroughly covered over a wide range of frequencies, bias points, and channel lengths. For the investigated frequency range, automotive and industrial applications have been reported [232].…”
Section: Contributionmentioning
confidence: 99%
“…Moreover, drain and gate current noise as well as their correlation are thoroughly covered over a wide range of frequencies, bias points, and channel lengths. For the investigated frequency range, automotive and industrial applications have been reported [232].…”
Section: Contributionmentioning
confidence: 99%